Environmental tax reform with irreversible investment, technological progress and unemployment - Christian M. Scholz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This paper analyzes if unemployment can be reduced through labor tax cuts that are financed in a revenue neutral way through energy tax increases. In contrast to other papers on this topic we consider investment behavior of firms in energy saving technologies, irreversibilities, embodied technological progress and involuntary unemployment. Arguments are presented that reducing the sunk costs instead of the labor tax seems to be the better instrument to reduce energy input and unemployment since this puts more pressure on firms that are using old technologies to adopt a more efficient energy saving technology.
Keywords: E60; H32; J3; J5; 330; Umweltabgabe; Energiesteuer; Steuerreform; Lohnsteuer; Angepasste Technologie; Energiesparen; Sunk Costs; Technischer Fortschritt; Investition